PQ4R-based E-LKPD to improve the fourth grade students’ higher order thinking skills - Linda Ratna Nirmala; Dwi Yulianti; Dina Maulina; Lilik Sabdaningtyas (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
This study is intended to analyze the need for e-LKPD development based on the preview, question, read, reflect, recite, and review (PQ4R) to improve students' HOTS. There are three syntaxes of 3-stage levels of high order thinking skills recommended by Bloom's taxonomy. It consists of analyzing, evaluating, and creating. The type of this research is a descriptive qualitative study analysis based on a literature review of e-LKPD and equipped with the PQ4R strategy as an effort to increase the HOTS of students. The research subjects were educators and fourth-grade students of SD Negeri 1 Purwosari, Padangratu Sub-District, Central Lampung. The research objects are HOTS, PQ4R, and e-LKPD. The data collection instrument used interview guidelines, questionnaires, and tests. The cause of the low HOTS of students is the inadequacy of teaching materials and learning strategies used in training HOTS abilities. The results of the study found that educators had not fully used e-LKPD teaching materials. Educational units also require learning strategies that can increase HOTS. PQ4R is one of the learning strategies that can be applied as a solution to increase students' HOTS. Educators need e-LKPD that contains PQ4R learning strategies that are following the characteristics of students. Thus, it can be concluded that the PQ4R-based e-LKPD to improve the HOTS of students in primary schools needs to be developed.